The Debate on Homosexuality in The Freewoman Journal (1911-12) - Florence Binard (Cahiers Victoriens et Edouardiens)
This article revisits the debate on homosexuality in the most controversial Edwardian feminist journal, The Freewoman, between January and April 1912. It shows that the taboo subject of female homosexuality, far from being absent from the debate in the pages of this journal, was a topic addressed in a daring and subversive manner. If the question of same-sex sexuality was indeed barely mentioned, the openness and frankness of the contributions point out to something far more subversive; it addressed issues that threatened the received « truths » of the time and paved the way to a deconstruction of the binary concepts of sex and gender.